Glinus oppositifolius (L.) Aug. DC.: A Repository of Medicinal Potentiality - Tania Chakraborty; Santanu Paul (International Journal of Phytomedicine, 2017)
Plants have been used in the treatment of human diseases since centuries. Due to their medicinal values, more than 80% of the modern world population still rely on plants as their primary source of medicines. Traditional plant-based medicines are widespread in Asian countries like the Indian subcontinent, Bangladesh, China, Japan, Pakistan, Indonesia, Myanmar, and in the continent of Africa. Nowadays, plant-derived medicines are gaining wider acceptance even in developed countries of the Western world. More than 50% of all drugs currently in clinical use are of natural origin. Plants are therefore emerging as a novel source for drugs and opening up new vistas in drug therapy research. A bird’s eye view of the therapeutic potential of the angiospermic plant Glinus oppositifolius (L.) Aug. DC. (Family: Molluginaceae) has been presented in this review, along with the ethnobotanical uses and scientific evidences presented in support of the traditional claims. Several pharmacologically active chemical compounds have been reported from the plant in recent years and the biological roles of those chemical compounds have been summarized. The anti-cancer effects shown by some of those phyto-constituents have also been elucidated. The novel chemical constituents reported from this plant may evoke further research on the plausible medicinal effects and the bio-safety standards of Glinus oppositifolius.